Shuntug : mga kabundukan sa kasaysayan at kalinangang Pilipino - 4 0 16; Ubaldo, Lars Raymund C.; 5 ADHIKA ng Pilipinas, Inc.,;National Commission on Culture and the Arts (Philippines) (Manila, Philippines : Adhika ng Pilipinas :;National Commission for Culture and the Arts, 2015)
Traditional belief of Philippine ethnic groups towards mountains.
Includes bibliographical references.
In Tagalog.
Keywords: 2 -- 0; 6; Ethnic groups;Mountains -- Philippines.;Philippines. -- 20; Religion. -- Philippines -- 20; 2